Study of Streptomyces extract as an effective inhibitor against microbiologically influenced corrosion by Pseudomonas aeruginosa biofilm on API 5L X52 steel - F, Bouchakour; E, Driche; T, Unsal; C, Fares; O.S, Taskın; A, Aksu; M, Sebaihia (International Research Journal of Multidisciplinary Technovation, 2026)
This research investigates the effect of a Streptomyces-derived extract (SE) on microbiologically influenced corrosion (MIC) induced by Pseudomonas aeruginosa biofilms on API 5L X52 steel. Various amounts of SE were evaluated in P. aeruginosa cultures by 7-day immersion assays. SE was extracted from Actinobacteria strains found in a soil sample from the Béchar-Kenadsa region of the Sahara. Gas chromatography-mass spectrometry (GC-MS) was utilized to analyze the chemical composition of the extract. This facilitated the identification of specific components that inhibit corrosion. The anticorrosion efficacy of SE against biofilm-induced corrosion under microbiological influence (CMI) of API 5L X52 steel caused by P. aeruginosa was assessed by potentiodynamic polarization (PDP) and electrochemical impedance spectroscopy (EIS). Scanning electron microscopy (SEM) was employed to examine the surface morphology. The findings indicate that the incorporation of SE significantly inhibits the development of P. aeruginosa biofilms on the coupons. This inhibitory activity leads to a significant reduction in the rate of microbiologically induced corrosion, commonly attributed to bacterial colonization.. In silico investigations validated that the discovered compounds exhibit a strong affinity for the corrosive bacterium P. aeruginosa, elucidating their inhibitory function.